Como se eu fizesse parte da aula: a relação entre uma proposta pedagógica ativa de ensino temático de inglês e a motivação de alunos do primeiro ano do Ensino Médio - Espino Prata, Sabrina (2023)
This study aimed at investigating the connection between an active learning methodology of theme-based English instruction and the motivation of High School freshmen in a technical public institution. Theme-based teaching, one of the possible Content-Based Instruction (CBI) models, attempts to meet students’ needs and interests, focusing on issues related to pedagogical or academic demands or cognitive preferences (DUEÑAS, 2004). Considering that many students do not manifest interest in learning the language after four years of studies in elementary school (CAMPOS-GONELLA, 2007) and the urgency for new routes for teaching after the creation of the Common National Curricular Base (BNCC – Brasil, 2018), the interest in this research is based on the great motivational appeal provided by this approach. Active learning methodologies bring together a framework of approaches, strategies and activities that allow students to work with autonomy and creativity in the construction and application of knowledge (NASCIMENTO; OLIVEIRA-MELO, 2022), assumptions that meet what is proposed by the Brazilian document. The study was based on the assumption that theme-based teaching, based on an active learning practice, can influence students' motivation to learn English, due to their responsibility for choosing the themes and researching materials for the elaboration of the classes, being, therefore, co-builders of the course. The research was conducted in two phases and the methodological procedure used was action-research, conducted with questionnaires, recording of classes and a research diary kept by the teacher-researcher. Data analysis revealed that the pedagogical practice adopted meets some conditions of Motivational teaching practice (DÖRNYEI, 2001) and was evidenced as favorable for acting on the level of the learners’ motivation, especially with regard to its differentiated dynamics, in addition to awakening the interest of students and favoring agency and student protagonism. Among the most influential factors in the participants' motivation, it can be highlighted the methodological and socio-environmental factors (VIANA, 1990), as well as the contingency factor, proposed in the development of this research. It is hoped that this study can contribute to contextualized language teaching focused on student's learning conditions, as Kumaravadivelu (2006) and Leffa (2012) argue, in which the learner is integrated to his environment and acts in the construction of his knowledge.